1982
DOI: 10.1128/jvi.43.2.594-607.1982
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus mRNA species mapping in EcoRI fragment I

Abstract: We described the detailed characterization and high-resolution mapping of nine herpes simplex virus type 1 mRNAs encoded in EcoRI fragment I. Four of these mRNAs are partially colinear and encode the same sized polypeptide in vitro. Nucleotide sequence analysis of the DNA around the 5' ends of these mRNAs suggested that the larger may encode a small (ca. 100-dalton) polypeptide not resolvable by in vitro translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 20 publications
8
72
0
Order By: Relevance
“…The gD coding sequence (394 codons) terminates approximately 100 bp upstream of the 1.6 kb early MM 5' terminus. The presence of families of 3' co-terminal mIm's has been previously described for other regicns of the HSV-1 genane (37,38,39). In sane instances, the snaller members of the family have been shcon to specify proteins fran coding sequences present in the 3' untranslated region of the larger members (37,40).…”
Section: Discussionmentioning
confidence: 81%
“…The gD coding sequence (394 codons) terminates approximately 100 bp upstream of the 1.6 kb early MM 5' terminus. The presence of families of 3' co-terminal mIm's has been previously described for other regicns of the HSV-1 genane (37,38,39). In sane instances, the snaller members of the family have been shcon to specify proteins fran coding sequences present in the 3' untranslated region of the larger members (37,40).…”
Section: Discussionmentioning
confidence: 81%
“…Our finding that the overrepresentation of 92/91K (VP11/ 12) in PREPs is 2.45-fold, compared with that in L-particles, argues for nonrandom incorporation of at least some tegument proteins during assembly of PREPs, because the early/late temporal classification of the UL46 gene (8,28) which encodes these proteins suggests that they should be present in reduced amounts in WT virus-infected cells treated with an inhibitor of viral DNA synthesis or in cells infected with the ambUL8 virus. Zhang and McKnight (28) have suggested that essential tegument proteins, such as VP16, provide a fixed framework around which nonessential proteins assemble.…”
Section: Discussionmentioning
confidence: 78%
“…Alternatively, if coordinate transcription of UL46 and UL47 occurs, the stoichiometry of these proteins relative to each other could be important. Since the transient-expression assays, unlike the current experiments, did not transcriptionally separate UL46 and UL47, but rather interrupted protein expression through the insertion of translational stop codons, the effect of putative coordinate transcription of these 3' coterminal mRNAs would not have been measured (15,34).…”
Section: Discussionmentioning
confidence: 85%